Effect of the alcoholic extract of the germander Basra lemon and red pepper in viability of Echinococcus granulosus protoscoleces of sheep origin in vitro - Aseel Esam Jamal Aldin; Ibrahim Ahmad Abdullah (College of Education for Pure Sciences, 2010)
ABSTRACT The results of the present study revealed significant effect of al-coholic extracts of the leaves of Teucrium polium; the fruits of Citrus aurantifolia and Capsicum annum at the concentrations 5, 10, 15, 20, 25 and 30 mg/ml for T. polium; the concentrations 2.5, 5, 7.5, 10, 12.5 and 15 mg/ml, for C. aurantifolia and the concentrations 1, 1.25, 1.5, 1.75, 2 and 2.25 mg/ml, for C. annum on the viability of the protoscoleces of Echinococcus granulosus of sheep origin in vitro. Hence the concentration 30 mg/ml for T. polium caused the death of all protoscoleces in 30, 45, 60 minuets, respectively, the concentration 25 mg/ml caused the same result in 60 minuets, while the concentration 15 mg/ml of C. aurantifolia reduced the viability of the protoscoleces to 10.33% in 60 minutes and the concentration 2.5 mg/ml of C. annum reduced the viability of the protoscoleces to 11.0% in 60 minutes.